Founder of the Lviv School of Statistical Physics and Builder of Ukrainian Statehood. To the Centenary of Ihor Yukhnovskii’ Birth (01.09.1925-26.03.2024) - W. Ebeling; Yurij Holovatch; Myroslav Holovko; I. Mryglod; O. Patsahan (Condensed Matter Physics, 2025)
September 1, 2025 marks the 100th anniversary of the birth of one of the Founding Fathers of the renewed Ukrainian state, a prominent Ukrainian scientist, theoretical physicist, founder of the modern Lviv school of statistical physics, Professor, full member of the National Academy of Sciences of Ukraine, full and honorary member of the Shevchenko Scientific Society, Hero of Ukraine, Ihor Yukhnovskii. He completed his earthly journey on March 26, 2024, in his 99th year of life. At the end of his eventful life, he pondered: “And now I no longer know what was most important to me in life — physics or politics?” Let us reflect on this issue as well.